THE EFFECT OF TURMERIC ON REDUCING DYSMENORRHEA IN ADOLESCENT GIRLS: SYSTEMATIC REVIEW - Sulaimah, Syifa; Siti Sukaesih, Nunung; Ningrum, Dedah (Buletin Veteriner Udayana, 2024)
The prevalence of menstrual problems worldwide is very high, with an average of more than 50% of women in each country suffering from menstrual problems. Menstrual pain or dysmenorrhea is sometimes referred to as symptomatic disease or malaise, which means it is not a disease, but rather a symptom that occurs which can cause discomfort. Efforts to overcome dysmenorrhea complaints include non-pharmacological therapy, one of which is turmeric which has herbal and traditional medicinal properties for various types of diseases. The aim of this paper is to examine and synthesize the results of existing research findings regarding the effect of giving turmeric on reducing dysmenorrhea in adolescent girls using a systematic review method. The article search used 4 databases, namely Google Scholar, PubMed, Semantic Scholar, and the Cochrane Library, resulting in 19 relevant articles for further review. The results of a research review of 19 articles stated that turmeric is a non-pharmacological therapy that can reduce dysmenorrhea in adolescent girls by containing many ingredients that are good for health. There was an effect of turmeric on reducing dysmenorrhea in young women and also changes in the pain scale before and after being given turmeric drinks.